Oxone® как безопасный и экологичный окислитель в синтезе иодониевых солей - Солдатова Н. С. Наталья Сергеевна; Постников П. С. Павел Сергеевич; Васильева К. А. Кристина Александровна; Кукурина О. С. Ольга Сергеевна; Юсубов М. С. Мехман Сулейман-оглы (Сулейманович) (2018, 2018)
Заглавие с экрана